The small molecule SI113 hinders epithelial‐to‐mesenchymal transition and subverts cytoskeletal organization in human cancer cells. Issue 12 (16th May 2019) - Abbruzzese, Claudia; Matteoni, Silvia; Persico, Michele; Ascione, Barbara; Schenone, Silvia; Musumeci, Francesca; Amato, Rosario; Perrotti, Nicola; Matarrese, Paola; Paggi, Marco G.
Abstract: The small molecule SI113 is an inhibitor of the kinase activity of SGK1, a key biological regulator acting on the PI3K/mTOR signal transduction pathway. Several studies demonstrate that this compound is able to strongly restrain cancer growth in vitro and in vivo, alone or in associative antineoplastic treatments, being able to elicit an autophagic response, either cytotoxic or cytoprotective. To elucidate more exhaustively the molecular mechanisms targeted by SI113, we performed activity‐based protein profiling (ABPP) proteomic analysis using a kinase enrichment procedure. This technique allowed the identification via mass spectrometry of novel targets of this compound, most of them involved in functions concerning cell motility and cytoskeletal architecture. Using a glioblastoma multiforme, hepatocarcinoma and colorectal carcinoma cell line, we recognized an inhibitory effect of SI113 on cell migration, invading, and epithelial‐to‐mesenchymal transition. In addition, these cancer cells, when exposed to this compound, showed a remarkable subversion of the cytoskeletal architecture characterized by F‐actin destabilization, phospho‐FAK delocalization, and tubulin depolimerization. These results were definitely concordant in attributing to SI113 a key role in hindering cancer cell malignancy and, due to its negligible in vivo toxicity, can sustain performing a Phase I clinical trial to employ this drug in associative cancer therapy. Abstract : SI113 is a small molecule able to inhibit the SGK1 kinase activity. Due to its powerful effect in restraining cancer cell growth and with the aim to provide a better comprehension of its mechanism of action, we used proteomic approaches to identify a spectrum of cellular targets of SI113 in cancer cells. These methodologies allowed us identifying novel putative targets of this compound, most of them involved in functions concerning cell motility and cytoskeletal architecture. Indeed, this compound was also proficient in inhibiting cell migration, invading properties, and epithelial‐to‐mesenchymal transition in a glioblastoma multiforme, hepatocarcinoma, and colorectal carcinoma cell line. Additionally, when these cells were exposed to SI113, a remarkable subversion of the cytoskeletal architecture was apparent. These results further attribute to SI113 a key role in hindering cancer cell malignancy and can sustain performing clinical trials to assay the possibility to use it in cancer therapy.